Advertising online by educational institutions and students’ reaction: a study of Malaysian Universities - Jan, Muhammad Tahir; Ammari, Djihane (Routledge, 2016)
This paper mainly aims to identify the impact of online advertising on students’ decision-making and their choice of higher education institutions. Data for this study were collected from 350 students from various Malaysian universities using self-administered questionnaires. The acquired data went through an exhaustive process to ensure that it was ready for analyses in SPSS and AMOS software. Factor analysis was used to extract the significant constructs underlying the data followed by a two-stage structural equation modeling in order to examine the fitness of the proposed model and test the hypotheses. The results revealed that social media and websites positively affect students’ decision- making, which then significantly impact students’ choice of a particular university. This research has invaluable implications for policy-makers, especially in the education industry of Malaysia. It is hoped that the findings of this study can be considered while making marketing plans for an educational institution.